2012
DOI: 10.1177/1468087412438472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an ethanol–diesel blend on a common-rail injection system

Abstract: This research paper presents a comparative experimental study for determining the functionality of a common-rail injection system used in light-duty diesel vehicles. Two Bosch fuel-injection systems were chosen to be tested using a low sulphur diesel fuel and an ethanol-diesel blend (7.7% v/v). Both systems were composed of a high-pressure injection pump Bosch (320 CDI), a common-rail and a Bosch piezoelectric fuel injector, and were tested during an accelerated durability test. In both cases, the injection sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
2
14
2
Order By: Relevance
“…This decrease in fuel delivery shows that the pump has lost ability to work, so further tests were discontinued. These results are contrary to the research results by Armas et al (2012) which show that the use of fuel blend with lower ethanol content (7.7% vol.) does not signally effect the durability of the common rail fuel pump.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This decrease in fuel delivery shows that the pump has lost ability to work, so further tests were discontinued. These results are contrary to the research results by Armas et al (2012) which show that the use of fuel blend with lower ethanol content (7.7% vol.) does not signally effect the durability of the common rail fuel pump.…”
Section: Resultscontrasting
confidence: 99%
“…Results show that the use of the ethanol-biodiesel-diesel blend tested produced a similar effect on the durability on the injection pump components studied and on the injector nozzle as that produced by diesel fuel. In another research Armas et al (2012) present durability test results of the high pressure fuel pump by using ethanol-diesel blend (7/7% v/v ethanol) without biodiesel. Results show that the use of the ethanol-diesel blend tested produced a similar effect on the durability of the injection pump parts as that produced when using diesel fuel.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, some of the major fuel properties such as cetane number, energy content, viscosity and lubricity of the diesel fuel are reduced by adding ethanol to the diesel fuel [8], therefore some significant problems can be observed in terms of combustion characteristics, especially low load conditions [6], engine durability and reduction in lubricity [9]. In the literature, limited studies have been conducted to solve these problems by adding cetane improvers [10] and biodiesel to the ethanol-diesel blends [11][12]. Biodiesel can be mixed with alcohol and fossil diesel without any cosolvent and emulsifiers [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, reduction in engine wear and increase in lubricity can be provided by the addition of biodiesel to fossil diesel fuel [17,18]. Armas et al [11] has studied the effect of ethanolbiodiesel-diesel blend (7.7 vol % ethanol (E), 27.69 vol % biodiesel (B) and 69.61 vol % (fossil diesel)) and pure fossil diesel fuel on the common rail injection system components. They found out that the used test fuels showed similar effects on the surfaces of the pump elements (drive shaft, cam and piston) independently.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the current solution implies the use of a small quantity of diesel -that anyway represents under 10% of the total amount of fuel supplied to the cylinder -for future solution the diesel fuel could be replaced with renewable solutions like dimethylether, which has been proved by many researchers to be a viable solution for diesel [2][3][4][5]. A survey of the available literature has showed that there are numerous studies about the use of ethanol fumigation [6][7][8][9] and diesel-ethanol blends [10][11][12][13][14][15], but very few studies that cover such a process that involves a separate direct injection of both fuels (diesel and ethanol), in which the diesel pilot injection is used to create the required conditions for the autoignition of a main ethanol injection, which is believed to be due to its higher complexity. The aim of this solution is to reduce the NO x and soot emissions, while taking advantage of the higher efficiency of the Diesel process.…”
Section: Introductionmentioning
confidence: 99%